Long-term outcomes following proton therapy for prostate cancer in young men with a focus on sexual health. (4th May 2018) - Ho, Clement K.; Bryant, Curtis M.; Mendenhall, Nancy P.; Henderson, Randal H.; Mendenhall, William M.; Nichols, Romaine C.; Morris, Christopher G.; Kanmaniraja, Dvaraju; Hamlin, Derek J.; Li, Zuofeng; Hoppe, Bradford S.
Abstract: Background: We investigated long-term outcomes for men ≤60 years old treated with proton therapy (PT). Methods: Of 254 men ≤60 years old were treated with proton therapy alone for prostate cancer. Risk stratification included 56% with low-, 42% with intermediate- and 2% with high-risk disease. Patients received 76–82 Gy at 2 Gy/fraction or 70–72.5 Gy at 2.5 Gy/fraction. Before treatment and every 6–12 months for 5 years, patients were evaluated by a physician, answered health-related quality of life surveys, including the EPIC, IIEF and IPSS, and had PSA evaluated. Results: Median follow-up for the cohort was 7.1 years; 7-year biochemical-free survival was 97.8%. Eight men (one high-risk; five intermediate-risk and two low-risk) experienced biochemical progression, including one who died of disease 9 years after treatment. Potency (erections firm enough for sexual intercourse) was 90% at baseline and declined to 72% at the first-year follow-up, but declined to only 67% at 5 years. Only 2% of patients developed urinary incontinence requiring pads. The bowel habits mean score declined from a baseline of 96 to 88 at 1 year, which improved over the following years to 93 at 5 years. Conclusions: Young men with prostate cancer continue to have excellent results with respect to 7-year biochemical control and 5-year erectile function, without clinically significant urinary incontinence 5 years after proton therapy. Comparative effectiveness studies of proton therapy with surgery and IMRT are needed.